2020
DOI: 10.1097/qad.0000000000002810
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV infection on baseline characteristics and survival of women with breast cancer

Abstract: Background: As women living with HIV (WLWH) become older, their risk of developing breast cancer increases. Nonetheless, literature is conflicting regarding tumor stage, distribution of subtypes and overall survival among WLWH vs HIV-negative women with breast cancer. We assessed differences in clinicopathological characteristics and overall survival between these two groups. Methods: Systematic review and meta-analysis using MEDLINE, Scopus, ISI Web of Knowledge, LILACS, SciELO and conference abstracts up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…7,8 In a metaanalysis of BC outcomes in SSA, Brandão et al showed that WLWH was diagnosed with BC at a more advanced stage and had worse OS (HR: 1.43; 95% CI: 1.06-1.92) than HIV-uninfected women. 9 We have found no data on receipt of BC treatment and ART, viral loads or CD4 counts among WLWH with BC in SSA.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…7,8 In a metaanalysis of BC outcomes in SSA, Brandão et al showed that WLWH was diagnosed with BC at a more advanced stage and had worse OS (HR: 1.43; 95% CI: 1.06-1.92) than HIV-uninfected women. 9 We have found no data on receipt of BC treatment and ART, viral loads or CD4 counts among WLWH with BC in SSA.…”
Section: Introductionmentioning
confidence: 84%
“…11-5.41) and SSA (HR: 1.43; 95% CI 1.06-1.92). 9 The reasons for these survival disparities are likely to be multifactorial. Many WLWH, both in South Africa and elsewhere, come from vulnerable populations at risk for poor cancer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, a double-fold increase in mortality among HIV positive patients with breast cancer was reported, with the hazard ratio range between 1.20 (95% CI, 1.14e1.26) and 2.93 (95% CI, 2.08e4.13) [25]. The recently published meta-analysis also revealed a poor overall survival among HIV positive women with breast cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the USA, a high cancer-specific mortality among HIV positive patients with breast cancer [HR 2.64; 96% CI 1.86e3.73] was reported [16]. A recently published meta-analysis also demonstrated that HIV positive patients had the worst overall survival when compared to HIV negative patients [17]. But none of the published studies specifically looked at the effect of ART use on the survival of breast cancer in HIV positive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, PLWH do not have an increased inci dence of cer tain com mon can cers, such as breast, colon, and pros tate can cer; how ever, they may pres ent at more advanced stages or with more aggres sive sub types. 5,6 NHL is the most com mon can cer among PLWH in the United States. 3 NHL is asso ci ated with mod er ate to severe immu no sup pres sion depending on the sub type (Figure 2).…”
Section: Cancers Aris Ing In Peo Ple With Hiv / Aidsmentioning
confidence: 99%